Long‐term oxidation and ablation behavior of Cf/ZrB2–SiC composites at 1500, 2000, and 2200°C. Issue 3 (29th December 2022) - Cheng, Yehong; Zhang, Fan; Ma, Denghao; Zhang, Yixin; Liu, Yaxiong; An, Yumin; Wang, Anzhe; Hu, Ning; Zhao, Libin; Han, Wenbo
Abstract: Although Cf /ZrB2 –SiC composites prepared via direct ink writing combined with low‐temperature hot‐pressing were shown to exhibit high relative density, high preparation efficiency, and excellent flexural strength and fracture toughness in our previous work, their oxidation and ablation resistance at high and ultrahigh temperatures had not been investigated. In this work, the oxidation and ablation resistance of Cf /ZrB2 –SiC composites were evaluated via static oxidation at high temperature (1500°C) and oxyacetylene ablation at ultrahigh temperatures (2080 and 2270°C), respectively. The thickness of the oxide layer of the Cf /ZrB2 –SiC composites is <40 μm after oxidizing at 1500°C for 1 h. The Cf /ZrB2 –SiC composites exhibit non‐ablative properties after oxyacetylene ablation at 2080 and 2270°C for >600 s, with mass ablation rates of 3.77 × 10 −3 and 5.53 × 10 −3  mg/(cm 2  s), and linear ablation rates of −4.5 × 10 −4 and −5.8 × 10 −4  mm/s, respectively. Upon an increase in the ablation temperature from 2080 to 2270°C, the thickness of the total oxide layer increases from 360 to 570 μm, and the carbon fibers remain intact in the unaffected region. Moreover, the oxidation and ablation process of Cf /ZrB2 –SiC at various temperatures was analyzed and discussed.